2023
DOI: 10.1097/yic.0000000000000517
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between mobile phone addiction and depression, anxiety, and sleep quality in medical students

Mahsa Nahidi,
Motahareh Ahmadi,
Mohammad Reza Fayyazi Bordbar
et al.

Abstract: This study investigates the prevalence of mobile phone addiction among medical students and its relationship with depression, anxiety, and sleep quality. The study was conducted at Mashhad University of Medical Sciences from 2019 to 2021, and it included medical students at four different levels of training. Participants were selected using a stratified random sampling method. All subjects completed the Mobile Phone Addiction Scale, Pittsburgh Sleep Quality Index (PSQI), Beck Depression Inventory, and Beck Anx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 84 publications
1
1
0
Order By: Relevance
“…Our findings align with previous reports indicating that medical college students with higher levels of cell phone addiction tend to experience poorer sleep quality ( 14 , 32 ). In the medical college student population, cell phone addiction can affect an individual's emotional self-control, emotional balance, and potentially leading to negative emotions such as anxiety or depression, all of which can impact sleep quality.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings align with previous reports indicating that medical college students with higher levels of cell phone addiction tend to experience poorer sleep quality ( 14 , 32 ). In the medical college student population, cell phone addiction can affect an individual's emotional self-control, emotional balance, and potentially leading to negative emotions such as anxiety or depression, all of which can impact sleep quality.…”
Section: Discussionsupporting
confidence: 92%
“…Studies have established a strong link between symptoms of cell phone addiction and the adverse effects it has on physical and mental health, particularly within the college student population ( 10 , 11 ). Additionally, research has shown a direct association between cell phone addiction and mental health issues, as well as the quality of sleep ( 12 14 ).…”
Section: Introductionmentioning
confidence: 99%